Analysis of Taste Image, Lifestyle, Word of Mouth, and Price on Interest to Buy the Electric Cigarette (VAPE) in the Millenial Generation in Panggkatan Village - Trisna Dianti; Bayu Eko Broto; Nurintan Asyiah Siregar (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine the effect of Taste Image, Lifestyle, word of mouth and price on interest in buying elektric cigarettes (Vape) in the millennial generation in Pangkatan Village. This type of research is explanatory research which explains the effect of one variabel on another through hypothesis testing. This study used a sample of 100 respondents are the millennial generation of pangkatan village who have used and known about electric cigarettes. This study used a sampling technique with a non-probability sampling method. Hypothesis testing is done by looking at the probability values and t-statistics. Data analysis used the statistical package for social sciences (SPSS) and assisted with SPSS 20 software. The results of this study show that simultaneously taste, lifestyle, word of mouth and price influence purchase intention with a significant value.